A Review of Recent reports on the Role of SSRI Use in Understanding the Pathomechanism and Treatment of Premenstrual Syndrome (PMS) as a Significant Clinical and Health Problem in Reproductive-Age Women - Jarczyńska , Patrycja; Fahim, Knieszko; Franaszek, Jakub; Herchi , Nadia; Jabrzyk, Martyna; Kijowski , Wojciech; Klusek , Mateusz; Michalak , Karolina; Przybył , Maciej (Quality in Sport, 2026)
Introduction. PMS affects 47% of women of reproductive age. It is a cyclical disorder responsible for somatic or mental symptoms during the luteal phase of the menstrual cycle. Etiology includes hormonal changes, GABA-A conduction disturbances, inflammation, genetic factors, and lifestyle. SSRIs are first-line medications used to treat severe PMS. Awareness of the pathomechanisms of the disease and the effects of treatment will allow us to better understand it, effectively treat it and minimize negative social and family consequences. Aim of the study. Discussion of the mechanism of action of SSRIs, with particular emphasis on more recent reports on the etiology and treatment of PMS in women of reproductive age. Materials and methods. A systematic review of the PubMed database from the last decade was conducted using the following keywords: PMS, PMDD, SSRI, allopregnanolone. Pediatric studies were excluded. Conclusions. SSRIs have a favorable safety profile, few adverse events, are effective at low doses with continuous and intermittent administration, and have a short half-life. The best-studied SSRIs to date are sertraline and fluoxetine, which have a beneficial effect on allopregnanolol levels and GABAergic conductance, as well as serotonin levels, which directly translates into a reduction in PMS symptoms in women of reproductive age. However, further research is needed to fully understand and utilize their mechanism of action in the symptomatic treatment of PMS.